Persepsi Dan Motivasi Mahasiswa Pendidikan Guru Sekolah Dasar (PGSD) Tentang Profesi Guru - Nurjannah Nurjannah; Sitti Rahmi (Universitas Negeri Makassar, 2022)
This study describes the perceptions and motivations students of Department of Primary Education concerning about the teaching profession along with the knowledge and experience they gained in college. The implications of the results of this study can provide a spectrum going forward so that Department of Primary Education study program managers can sustainably develop teacher professional programs to strengthen the identity of students as teacher candidates. This type of research is qualitative descriptive. The method used in this study is a survey method using an open questionnaire. The subjects of this study were 36 students of Department of Primary Education, University to the students of PGSD S1 Campus V Makassar Negeri University City Pare – Pare in. The results showed all respondents stated that this profession is a noble profession, but they can switch to other jobs if income is more adequate. 83.33% of respondents said they were ready to become teachers while 16.67% said they were not ready to go into the field independently.